2019
DOI: 10.3390/medicines6030078
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds as New Cancer Treatments

Abstract: Cancer is still a global challenge worldwide with a high impact not only on human health, causing morbidity and mortality, but also on economics [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Was obtained as a yellow solid (79 % yield). 1 H and 13 C NMR spectra of 3,4-DHPEA-EA and 3,4-DHPEA-EA (P) were in agreement with literature data [7]. 1 H and 13 C NMR spectra were recorded at 300 and 75 MHz respectively in CDCl3 using tetramethylsuilane (TMS) as internal standard on a Bruker ACP 300 MHz instrument.…”
Section: Synthesis Of 34-dhpea-ea and 34-dhpea-ea (P)supporting
confidence: 84%
See 1 more Smart Citation
“…Was obtained as a yellow solid (79 % yield). 1 H and 13 C NMR spectra of 3,4-DHPEA-EA and 3,4-DHPEA-EA (P) were in agreement with literature data [7]. 1 H and 13 C NMR spectra were recorded at 300 and 75 MHz respectively in CDCl3 using tetramethylsuilane (TMS) as internal standard on a Bruker ACP 300 MHz instrument.…”
Section: Synthesis Of 34-dhpea-ea and 34-dhpea-ea (P)supporting
confidence: 84%
“…Oleuropein is the main phenolic compounds of olive leaves and an important bioactive compound with various biological properties including anticancer [1], antidiabetic and antiatherosclerotic [2]. Moreover, several in vitro and in vivo studies indicate that oleuropein is a potent superoxide anion and other reactive oxygen species (ROS) scavenger [3].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have always been an indispensable and important source in the development of innovative therapeutic drugs for a wide range of diseases, including cancer [ 12 , 13 , 14 , 15 ]. Ursolic acid (UA, 3β-hydroxy-12-urs-12-ene-28-oic-acid) is present in various fruits and vegetables and is a crucial part of the human diet [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients facing cancer, in addition to various forms of treatment recommended by their doctors, use a variety of dietary supplements to help their body fight the disease. Among minerals, these will undoubtedly include zinc (2)(3)(4) and selenium (5,6) and among biologically active substances, polyphenolic compounds (including resveratrol and genistein) (7)(8)(9). Both in vitro studies on human cancer cells and in vivo studies on rodents have shown that zinc can inhibit the proliferation of certain types of tumour cells, while zinc deficiency increases cell proliferation and promotes inflammation (10,11).…”
mentioning
confidence: 99%
“…The role of zinc in the prevention of cancer is the result of antioxidant activity, which protects against DNA damage, and the complex effect of zinc on the immune system (induction of IL-1, IL-6, TNF-alpha, and monocytes, T cell differentiation; and others) (10,11). Polyphenolic compounds exert an anti-carcinogenic effect not only through the immune system, but also by influencing the cell cycle, apoptosis, angiogenesis and metastasis (7)(8)(9)13). Numerous studies have shown them to be promising agents in chemotherapy and other cancer treatments, alone (14,15) or in combination with existing chemotherapeutics (16,17).…”
mentioning
confidence: 99%